Utilización de módulos gps en combinación con módulos de radio frecuencia para la transmisión de datos de posicionamiento hacia control central empleando microcontroladores - Aguirre Salas, Valeria (2011)
Nowadays, we have available a large amount of technological resources covering priority needs. One of them is the localization of objects and persons, aiming this purpose it is used the Global Positioning System GPS. The application of this technology is extensive, ranging from control positioning systems and mobile robotic applications, to simple goals as vehicle location and some sporting purposes. For that reason, in this project it was proposed and carried out the interaction of positioning data acquired thru a GPS receiver acquiring NMEA sentences, in combination with other technologies as microcontrollers and transmissions using radio frequencies.